Faktor-Faktor yang Berhubungan dengan Pemberian Kolostrum pada Bayi Baru Lahir di Puskesmas Curug Kota Serang Provinsi Banten tahun 2018. - Leni Halimatusyadiah (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Kesehatan Salsabila Serang, 2019)
In order to reduce child morbidity and mortality, the United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) recommend giving colostrum immediately after birth and exclusive breastfeeding until the baby is 6 months old (Depkes RI, 2014). The Government of Indonesia through the Decree of the Minister of Health Number 450/SK/Menkes/VIII/2004 dated April 7, 2004 has determined exclusive breastfeeding for 6 months to mothers in Indonesia. (Infodatin, 2014). The purpose of this study was to determine the factors associated with giving colostrum to newborns at the Curug Health Center, Serang City, Banten Province in 2018. In this study, the authors used this type of research using observational analytics. The research method used is cross sectional. The population used in this study were mothers who gave birth normally at the Curug Health Center in Banten Province, amounting to 38 in October 2018. In this study, the sampling technique used was accidental sampling. The results of statistical research using chi-square showed that the knowledge and family support variables were associated with giving colostrum to newborns with p-values ??of (0.001 < (0.05) and (0.004 < (0.05). in order to increase knowledge, insight and seek as much information as possible about the benefits of breastfeeding, especially colostrum breast milk and it is hoped that mothers can improve relationships between individuals both with family and friends who can later share information, experiences and support each other in breastfeeding their children.